Unnoticed sedentary life style, ingestion of junk food, and cigarette smoking: Cause heart problems - Dr Shah Murad (Journal of Medical Biomedical and Applied Sciences, 2023)
When patient get sick, he/she has to treat his/her disease, and every prescribed allopathic medicine has its own adverse effects. Dyslipidemia is that disease which if not treated, leads to develop complications like heart, arteries, thyroid, liver, and kidney diseases commonly called metabolic syndrome. To treat metabolic syndrome is again has its limitations, like prolonged and combined treatment with different drug groups. Just to change sedentary life style and eating habits prevents from all above mentioned problems. Just look at regular intake of two fruits ie; apple and apricot may help to escape patients from sufferings related to hyperlipidemia. These two fruits have had been researched by scientist for treatment of hyperlipidemia by decreasing low density lipoprotein cholesterol (LDL-C) and increasing high density lipoprotein cholesterol (HDL-C). Research Design/sample size/consent: It was placebo based research work conducted at General Hospital Lahore from January to April 2016. 100 already diagnosed patients of primary/secondary hyperlipidemia were enrolled in research study with (written/explained and approved) consent. Inclusion/exclusion criteria: Inclusion criteria was their age (20-70 years), gender (male and female) and patients not on any hypolipidemic allopathic medicines. Exclusion criteria was smokers, alcoholic addictives, and patients of thyroid, liver, lung, and severe heart related diseases. Grouping: They were divided in four equal groups including 25 patients in each group. Group-one was on apple half kg per day for the period of three months. Group-two was on apricot half kg per day for the period of three months. Group-three was on apple ½ kg plus apricot ½ kg for the period of three months. Group-four was placebo group and they were advised to take any fruit except these two fruits ie; apple and apricot. Method: Their name/age/gender/occupation/address/cell number was kept in separate folder for research record. Their base line lipid profile was determined at pathology/biochemistry laboratory of the hospital. Fortnightly visit was advised to them. After three months therapy their lipid profile was re-determined. Mean values of their LDL-C and HDL-C ± SEM was analyzed biostatistically by applying paired t-test. P-values >0.05 was regarded as non-significant, p-values <0.01 and <0.001 were regarded as significant and highly significant changes in tested parameters respectively. Results: After three months therapy it was observed that apple reduced LDL-cholesterol 23.77 mg/dl and increased HDL-cholesterol 3.3 mg/dl. Apricot reduced LDL-cholesterol 7.5 mg/dl and increased HDL-cholesterol 5.3 mg/dl. Combination of both fruits decreased LDL-cholesterol 16.1 mg/dl and increased HDL-cholesterol 6.6 mg/dl in three months therapy. Conclusion: It was concluded from results of this research work that apple and apricot given separately or in combination, have remarkable effect on LDL-C and HDL-C in patients suffering from primary/secondary hyperlipidemia.